Informe de la Comision de Estudio e Informacion de la Conferencia internacional de estudiantes. . Informes sobre la educacion superior en
Till 1960 titled: Informes sobre la educacion superior .... (in: CEI anales, Anales de la RIC). - Also publ. in English and French. In the IISH-holdings the English, Spanish and French reports are put together, and chronologically ordered according to the conferences.